The fecal metabolome and microbiome are altered in dogs with idiopathic epilepsy compared to healthy dogs - Fien Verdoodt; Myriam Hesta; Evy Goossens; Filip Van Immerseel; Jenifer Molina; Luc Van Ham; Lynn Vanhaecke; Lieselot Y. Hemeryck; Sofie F.M. Bhatti (Scientific Reports)
Abstract Idiopathic epilepsy (IE) is the most common chronic neurological disease in dogs, and a natural animal model for human epilepsy types with genetic and unknown etiology. The microbiota-gut-brain axis (MGBA) is a promising target for improving brain health in individuals where brain function is hampered. It’s role in the pathophysiology of epilepsy remains however unclear. We aimed to identify differences in fecal metabolome and microbiome between healthy and dogs with IE. To this purpose, fecal samples of healthy (n = 39) and dogs with IE (n = 49) were metabolically profiled (n = 148 metabolites) and fingerprinted (n = 3690 features) using liquid chromatography coupled to mass spectrometry, and the bacterial phylogeny examined using 16 S rRNA sequencing. Dogs with IE were categorized as drug-resistant (DR) (n = 27) or mild phenotype (MP) (n = 22). In dogs with DR IE compared to healthy, fecal metabolites such as histamine (P = 0.022) and microbiome genera such as Escherichia-Shigella (P = 0.021) increased, associated with a proinflammatory environment. In dogs with MP IE compared to healthy, alterations associated with anti-inflammatory properties, such as increased fecal serotonin (P = 0.034) and Blautia hominis (P = 0.012) were revealed. Overall, a role for the MGBA communication in canine IE was established.